Phytonutritional Content and Aroma Profile Changes During Postharvest Storage of Edible Flowers - Marchioni, Ilaria; Pistelli, Laura; Ferri, Benedetta; Copetta, Andrea; Ruffoni, Barbara; Pistelli, Luisa; Najar, Basma (Frontiers in Plant Science, 2020)
Edible flowers are niche horticultural products, routinely used as cooking ingredients in the food industry. Currently, new species are introduced aimed at the presence of their bioactive compounds and for innovative fragrance and taste. Flowers of different families (Asteraceae, Geraniaceae, Lamiaceae) have been examined to evaluate some nutritional properties and flavor characteristics to increase the demand of novel varieties, according to the objectives defined in the INTERREG ALCOTRA “ANTEA” project. The four species of Ageratum houstonianum Mill., Tagetes lemmonii A. Gray, Salvia dorisiana Standl and Pelargonium odoratissimum (L.) L’Hér ‘Lemon’ were selected for their different taste and color. Fresh flowers were cold stored at 4 °C for two and six days in plastic bags, and cellular membrane damage was observed. The relative content of different phytochemicals (e.g. polyphenols, flavonoids, anthocyanins, ascorbic acid and soluble sugars), the radical scavenging activity and the volatile profile were determined and correlated to the quality of shelf-life of the different species. The yellow T. lemmonii flowers showed the highest ascorbic acid, polyphenols and flavonoids content, maintained during the cold storage. Limited changes of metabolites were detected in the light blue A. houstonianum during postharvest, while antioxidant compounds adversely changed in magenta S. dorisiana and light pink P. odoratissimum. For the first time the volatile compounds have been identified in the four species. The cold storage influenced mainly P. odoratissimum and S. dorisiana flavor initially dominated by total sesquiterpenes than converted to total monoterpenes at the 6 days of the postharvest. Both A. houstonianum and T. lemmonii conserved the prevalence of the same class of constituents in all the analysed conditions, even though the cold storage influenced the major compound abundance. New compounds were biosynthesized during the storage at low temperature suggesting an involvement in the alteration in cellular physiology. S. dorisiana flowers appeared the most sensitive species to cold stress, while T. lemmonii was the most interesting species with the longest shelf-life. Results support the hypothesis that the different species endorse the physiological biodiversity of the flowers and can differently affect the organoleptic characteristics of their shelf-life.